Topical application of ointment containing 0.5% green tea catechins suppresses tongue oxidative stress in 5-fluorouracil administered rats. (October 2017) - Miyai, Hisataka; Maruyama, Takayuki; Tomofuji, Takaaki; Yoneda, Toshiki; Azuma, Tetsuji; Mizuno, Hirofumi; Sugiura, Yoshio; Kobayashi, Terumasa; Ekuni, Daisuke; Morita, Manabu
Highlights: Oral mucositis is one of the side effect in administration of 5-fluorouracil. Oxidative stress induced by 5-fluorouracil is an initiator of oral mucositis. Catechins have antioxidant activity. Catechins could prevent oxidative stress, with up-regulating Nrf2 signaling pathway. Abstract: Objective: The purpose of this study was to investigate the preventive effects of topical application of green tea catechins on tongue oxidative stress induced by 5-fluorouracil (5-FU) administration in rats. Design: Male Wistar rats (n = 28, 8 weeks old) were divided into four groups of seven rats each: a negative control group (saline administration and application of ointment without green tea catechins), a positive control group (5-FU administration and application of ointment without green tea catechins), and two experimental groups (5-FU administration and application of ointment containing 0.1% or 0.5% green tea catechins). Topical application of each ointment to the ventral surface of the tongue was performed once a day for 5 days. The level of 8-hydroxydeoxyguanosine (8-OHdG) was determined to evaluate oxidative stress. Fluorescence staining was also performed to confirm nuclear factor erythroid 2-related factor 2 (Nrf2) translocation to the nucleus. Results: After the experimental period, the ratios of 8-OHdG-positive cells in the ventral tongue tissue were higher in the positive control group than in the negative control group ( P  < 0.05). On the other hand, those in the 0.5% green tea catechin group, but not in the 0.1% green tea catechin group, were lower than the positive control group ( P  < 0.05). In addition, Nrf2 translocation to the nucleus was greater in the 0.5% green tea catechin group than in the positive control group ( P  < 0.05). Conclusions: Topical application of ointment containing 0.5% green tea catechins could prevent tongue oxidative stress in 5-FU administered rats, via up-regulation of the Nrf2 signaling pathway.